Implementation of Passive Range of Motion (ROM) Exercises to Improve Muscle Strength in Non-Hemorrhagic Stroke Patients in the MTSK Ward of BLUD RSUD Baubau City - Sri Resky Mustafa; Nurfatima; Fadila Masrika (Public Health and Safety International Journal, 2026)
Non-hemorrhagic stroke is a condition characterized by the loss of neurological function due to impaired blood flow to the brain, which results in muscle weakness and impaired physical mobility. This study aims to determine the effectiveness of passive Range of Motion (ROM) exercises in improving muscle strength in patients with non-hemorrhagic stroke. The study used a descriptive case study design involving one adult patient experiencing impaired physical mobility. The intervention consisted of passive ROM exercises administered for five consecutive days. The theoretical approach applied includes physical rehabilitation theory and the concept of basic human needs, with inputs consisting of the patient’s clinical condition and pre-intervention muscle strength values. Data were collected through observation and measurement using a muscle strength scale. The results showed an increase in muscle strength of the right upper extremity from grade 1 to 5, and the right lower extremity from grade 1 to 5 after the intervention. The hypothesis that passive ROM exercises can improve muscle strength was supported. It is concluded that passive ROM exercises are effective in increasing muscle strength in non-hemorrhagic stroke patients. Nurses are recommended to implement this intervention as part of nursing care. These findings are important as a basis for simple and effective interventions to improve the quality of life of stroke patients.